TINJAUAN HUKUM ISLAM TERHADAP WALIMATUL ‘URSY DI RUMAH GADANG (Studi di Nagari Abai Kecamatan Sangir Batang Hari) - Hengki Saputra; Nailur Rahmi (Institut Agama Islam Negeri Batusangkar, 2021)
This study examines walimatul ursy. The problem is the walimatul 'ursy in the gadang house in Nagari Abai, Sangir Batang Hari District, South Solok Regency. From these problems the question arises how the process of implementing the walimatul 'ursy tradition at the gadang house in Nagari Abai, Sangir Batang Hari District, South Solok Regency. This research is a field research (Field Research). Data obtained through interviews and documentation. Furthermore, the data is narrated descriptively. The results are discussed with the proposed theories. This study found that walimatul 'ursy in the rumah gadang is a tradition carried out with the terms and conditions that have been applied and to carry out it must obtain permission from the datuak who leads the tribe and from the Datuak Fourteen. Meanwhile, according to Islamic law, the tradition of doing walimatul 'ursy at the rumah gadang is categorized as something good which is a symbol of the condition of the bride and groom and the bride's family, so it can be classified as maslahah.